#TITLE_ALTERNATIVE# - HANRY SITOMPUL (NIM : 10208100); Pembimbing : Gunawan Handayani, MSCE, Ph.D, DANIEL
Damage that occurs will reduce the structural strength to withstand the load. Therefore, tests were carried out after the implementation of the manufacture of construction to ensure the integrity of the pile is needed. Common methods used for testing is Low strain pile Pile Integrity Test is more known as PIT. By using this test, the low-frequency impulses given at the end of the pile with a hammer and the speed of the tip of the stake can be observed by using the accelerometer. Impulses with frequency crumb will generate waves with low frequencies that will propagates along the pile and is reflected in the place where. Analysis carried out in this thesis is an analysis using the frequency domain. Where then is converted from the time domain into the frequency domain to make use of the Fast Fourier Transform (FFT). Processing with PIT method is relatively easy and fast, and allows for test piles in large quantities in a short time.